2014
DOI: 10.1149/2.055406jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lithium Content and Surface Area on the Electrochemical Performance of Li1.2Mn0.54Ni0.13Co0.13O2

Abstract: Lithium-rich, layered composites of xLi 2 MnO 3 •(1-x)LiNi 1/3 Mn 1/3 Co 1/3 O 2 have been extensively studied for PHEVs and EVs. To ensure complete lithiation, most synthesis methods require the addition of excess lithium compared to the stoichiometric composition. In this study lithium enriched, layered composites of Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 were synthesized in a spray pyrolysis process. Spray pyrolysis allows for excellent control of composition and in this work the lithium content was systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…Even for materials prepared at conditions 2 and 3, where the as-prepared NCM811 particles had a defined (if irregular) micron-scale single-particle morphology, annealing causes this structure to collapse. A similar overall morphological change for long annealing times (10–20 h) of Li-rich Li 1.28 Mn 0.54 ­Ni 0.13 Co 0.13 O 2 powders prepared using spray pyrolysis has also been noted . For the layered NCM811 synthesized here, we confirmed that annealing for a shorter duration (4 h) or reducing the Li content in the precursor solution does not noticeably affect the observed changes.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Even for materials prepared at conditions 2 and 3, where the as-prepared NCM811 particles had a defined (if irregular) micron-scale single-particle morphology, annealing causes this structure to collapse. A similar overall morphological change for long annealing times (10–20 h) of Li-rich Li 1.28 Mn 0.54 ­Ni 0.13 Co 0.13 O 2 powders prepared using spray pyrolysis has also been noted . For the layered NCM811 synthesized here, we confirmed that annealing for a shorter duration (4 h) or reducing the Li content in the precursor solution does not noticeably affect the observed changes.…”
Section: Resultssupporting
confidence: 86%
“…Using such a process, examples of cathode materials that have been produced are spinel LiMn 2 O 4 and LiNi 0.5 Mn 1.5 O 4 , Li-rich materials, LiCoPO 4 -C composites, and layered LiNi 0.33 Co 0.33 ­Mn 0.33 O 2 (hereafter referred to as NCM111), , using precursor solutions which are atomized into droplets on the 1–10 μm scale and delivered to self-supporting flames or tube furnaces. Several observations can be made.…”
Section: Introductionmentioning
confidence: 99%
“…In our eyes, these applications should cut across many fields, beyond just energy- developments in measurement, modeling, and integration with process control will further enable the development of flame aerosol reactor systems to produce the nanomaterials and devices that will impact society. [49] Lithium acetylacetonate 250 toluene [52] lithium nitrate 253 methanol [50] water [46]; [48];…”
Section: Discussionmentioning
confidence: 99%
“…xylene:tetrahydrofuran=1:1 [140] Cobalt naphthenate mineral spirits/xylene [351]; [361] Cobalt(II) nitrate(+4H2O,+6H2O) 100 1-propanol [148] 55 +6H2O) Ethanol [141]; [148] Methanol [148] methanol:propionic acid=1:1; ethanol:propionic acid=1:1; 1-propanol:propionic acid=1:1; propionic acid/1-octanol; propionic acid/1-pentanol [148] Water [46]; [48] Cobalt [154] Water [46] Nickel(II) propionate water/propionic acid [153] Nickel [109]; [162]- [164] xylene:acetonitrile=1:1 [367] Copper Ethanol [161] Isopropanol [168] Water [49]; [157] water/citric acid(as the chelating agent) [166] Copper propionate water/propionic acid [44]; [45] Zinc naphthenate Ethanol [106]; [169]; [170] Toluene [52]; [468] toluene:acetonitrile=4:1 [171] toluene:acetonitrile=8:1 [466] [467] Toluene:methanol=7:3 [172] Methanol:acetic acid=1:1 [80] mineral spirits/xylene [427] Zinc water/acetic acid [133] water/nitric acid [179] Strontium chloride 874 water/nitric acid [179] Strontium nitrate 570 Dimethylformamide [108] dimethylformamide:ethanol=4:1 [108] Water…”
Section: -170mentioning
confidence: 99%
See 1 more Smart Citation